2009
DOI: 10.1017/s0033291708004984
|View full text |Cite
|
Sign up to set email alerts
|

Impaired inhibitory control is associated with higher-order repetitive behaviors in autism spectrum disorders

Abstract: Background-Impairments in executive cognitive control, including a reduced ability to inhibit prepotent responses, have been reported in autism spectrum disorders (ASD). These deficits may underlie patterns of repetitive behaviors associated with the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
170
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(197 citation statements)
references
References 46 publications
(58 reference statements)
18
170
1
1
Order By: Relevance
“…Finally, Mosconi et al (2009) presented adults with ASD and ageand IQ-matched TD peers with a Gap-Overlap task in which targets were presented at three different visual angles in the periphery. Participants were instructed to look towards the peripheral target as soon as it appeared, and visual orienting was measured using EOG during Gap and Overlap trials.…”
Section: Studies During Childhood and Adulthoodmentioning
confidence: 99%
“…Finally, Mosconi et al (2009) presented adults with ASD and ageand IQ-matched TD peers with a Gap-Overlap task in which targets were presented at three different visual angles in the periphery. Participants were instructed to look towards the peripheral target as soon as it appeared, and visual orienting was measured using EOG during Gap and Overlap trials.…”
Section: Studies During Childhood and Adulthoodmentioning
confidence: 99%
“…verbal fluency) in a sample of young people with ASD. Mosconi et al (2009) reported that impaired inhibition of prepotent responses was related to increased severity of higher order Tager non-verbal ability; OCD: obsessive compulsive disorder; PDD-NOS: pervasive developmental disorder-not otherwise specified; PIQ: performance intelligence quotient; PLI: pragmatic language impairment; r: correlation coefficient; R 2 : coefficient of determination; RBS-R: Repetitive Behaviour Scale-Revised; RRBIs: restricted and repetitive behaviours and interests; SCQ: Social Communication Questionnaire; SLI: specific language impairment; SRS: Social Responsiveness Scale; TD: typically developing, ToM: Theory of Mind; VA: verbal ability; VABS: Vineland Adaptive Behaviour Scales; VIQ: verbal intelligence quotient. Cohen's d, Pearson's correlation coefficient r and R 2 are reported to convey effect sizes.…”
Section: Executive Functions and Asd Symptomsmentioning
confidence: 99%
“…lower-level repetitive behavioural patterns), but not Asperger disorder. For example, repetitive behaviours in autism may result from impaired inhibition, 26 whereas such behaviour in Asperger disorder could result from a failure to 'spontaneously generate novel behaviour without prompting' 27 (p 843) (reflecting higher-level repetitive behaviours, including circumscribed interests), although this hypothesis requires further investigation (see Rinehart et al 5 for a review).…”
Section: P 195)mentioning
confidence: 99%